2017
DOI: 10.1146/annurev-cellbio-100616-060847
|View full text |Cite
|
Sign up to set email alerts
|

Sending and Receiving Hedgehog Signals

Abstract: Communication between cells pervades the development and physiology of metazoans. In animals, this process is carried out by a relatively small number of signaling pathways, each consisting of a chain of biochemical events through which extracellular stimuli control the behavior of target cells. One such signaling system is the Hedgehog pathway, which is crucial in embryogenesis and is implicated in many birth defects and cancers. Although Hedgehog pathway components were identified by genetic analysis more th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
74
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 181 publications
(207 reference statements)
2
74
0
Order By: Relevance
“…In E. granulosus, it was demonstrated that fructose-bisphosphate aldolase interacts with actin[41].Proteins acting in signaling pathways were identified in our analyses, many of them shared between E. granulosus and E. ortleppi. Desert hedgehog protein (Dhh), noggin, notch, tyrosine protein kinase otk and glypican-1 are examples of signaling proteins that play crucial roles in embrionary and morphological development in model organisms, such as Caenorhabditis elegans, Drosophila melanogaster and Mus musculus[45][46][47][48]. The germinative layer in fertile metacestodes is constituted of cells that actively participate in cyst development, these cells differentiate to generate brood capsules and PSC, secrete part of HF components and produce the molecules needed to maintain cyst wall integrity[6,49].…”
mentioning
confidence: 99%
“…In E. granulosus, it was demonstrated that fructose-bisphosphate aldolase interacts with actin[41].Proteins acting in signaling pathways were identified in our analyses, many of them shared between E. granulosus and E. ortleppi. Desert hedgehog protein (Dhh), noggin, notch, tyrosine protein kinase otk and glypican-1 are examples of signaling proteins that play crucial roles in embrionary and morphological development in model organisms, such as Caenorhabditis elegans, Drosophila melanogaster and Mus musculus[45][46][47][48]. The germinative layer in fertile metacestodes is constituted of cells that actively participate in cyst development, these cells differentiate to generate brood capsules and PSC, secrete part of HF components and produce the molecules needed to maintain cyst wall integrity[6,49].…”
mentioning
confidence: 99%
“…ligands through tissues has been thoroughly reviewed recently (Manikowski et al, 2018;Petrov et al, 2017). Regulation of secretion and transport is important for shaping temporal and spatial gradients of HH ligands across developing tissues, signaling strength in target cells and consequently tissue patterning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The TM protein Dispatched (DISP1) is required exclusively for ligand release and likely functions to isolate HH ligands from the bulk membrane by binding to their cholesteroyl moieties and transferring them to a carrier for transport through tissues (Burke et al, 1999;Caspary et al, 2002;Kawakami et al, 2002;Ma et al, 2002;Tukachinsky et al, 2012). Several types of carriers have been identified, including the Scube family of secreted proteins, lipoproteins, extracellular vesicles and multimers of ligands themselves (summarized by Petrov et al, 2017). A distinct solution to the ligand transport problem is provided by cytonemeslong, actin-based cellular extensions that directly deliver ligands to distant cells without the requirement for ligand release from membranes (Bischoff et al, 2013;Chen et al, 2017;Ramírez-Weber and Kornberg, 1999;Sanders et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Hedgehog (Hh) precursor undergoes autocatalytic processing, and the resulting Nterminal signaling domain is modified with N-terminal palmitoylation and C-terminal and tissue homeostasis [4][5][6] . Deficient Hh signaling can lead to birth defects, whereas abnormal Hh signaling activation is associated with various human cancers [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%